Collaborative Chronic Care Networks (C3Ns) to Transform Chronic Illness Care - Margolis, Peter A. (American Academy of Pediatrics, 2013)
Despite significant gains by pediatric collaborative improvement networks, the overall US system of chronic illness care does not work well. A new paradigm is needed: a Collaborative Chronic Care Network (C3N). A C3N is a network-based production system that harnesses the collective intelligence of patients, clinicians, and researchers and distributes the production of knowledge, information, and know-how over large groups of people, dramatically accelerating the discovery process. A C3N is a platform of “operating systems” on which interconnected processes and interventions are designed, tested, and implemented. The social operating system is facilitated by community building, engaging all stakeholders and their expertise, and providing multiple ways to participate. Standard progress measures and a robust information technology infrastructure enable the technical operating system to reduce unwanted variation and adopt advances more rapidly. A structured approach to innovation design provides a scientific operating system or “laboratory” for what works and how to make it work. Data support testing and research on multiple levels: comparative effectiveness research for populations, evaluating care delivery processes at the care center level, and N-of-1 trials and other methods to select the best treatment of individual patient circumstances. Methods to reduce transactional costs to participate include a Federated IRB Model in which centers rely on a protocol approved at 1 central institutional review board and a “commons framework” for organizational copyright and intellectual property concerns. A fully realized C3N represents a discontinuous leap to a self-developing learning health system capable of producing a qualitatively different approach to improving health.